EPIDEMIOLOGICAL RELATIONSHIPS AMONG STRAINS OF Salmonella enterica subsp. enterica, ISOLATED FROM HUMANS, POULTRY AND FOOD (2006)
Human gastro-enteritis caused by Salmonella enterica is a major health problem in developing countriessuch as Colombia. In some parts of Colombia, the disease is endemic, and its incidence appears to beincreasing, with outbreaks and sporadic cases of diarrhea becoming more frequent. At this time, it is notvery clear if either poultry or food is responsible for human salmonellosis contamination in Colombia.The objectives of the present study were to analyze the Pulsed-field gel electrophoresis profiles (PFGEPs) of Salmonella enterica from human patients, poultry and food found in Colombia and to determine theepidemiologic associations between these strains. Twenty-nine isolates of Salmonella enterica subsp.enterica were isolated from: 10 pediatric patients in Bogotá, D.C., 10 different types of food and 9chickens. All isolates were analyzed by means of the molecular technique XbaI PFGE. Eleven differentpatterns were observed. These patterns consisted of 12-17 restriction fragments, each with a molecularsize of 30-800 kb. The results suggested that Salmonella enterica was transmitted from poultry and foodto humans. Surprisingly, among the strains investigated it was impossible to find a direct linkage betweenpoultry and food, indicating, either that Salmonella was incorporated into the food during food processingby handlers, or that foods other than poultry products were the source of human infection. This studyabout the molecular epidemiology of Salmonella enterica in Colombia provided new information aboutpossible means of human contamination, and should permit health institutions to take adequate measuresto avoid sporadic cases and outbreaks of salmonellosis.